Srī dasama grantha sāhiba saṭīka - Bishana Siṅgha (SAMP early 20th-century Indian books project ;, 1941)
Commentary on Dasweṉ Pādshāsh kā Granth, sacred work of Sikhs, attributed to Guru Gobind Singh, 1666-1708.